Groundwater issues in eastern India - Pant, Niranjan (International Food Policy Research Institute, 1990)
Different official documents and reports have treated eastern India differently. For the purposes of the present chapter, eastern India is defined to include the states of Assam, Bihar, Orissa, West Bengal, and 15 districts of eastern Uttar Pradesh. The region contains a population of about 212 millisn, representing 31 percent of India's population. Although endowed with rich natural resources, the region lags behind others ii agricultural, industrial, and technological developments. Its popilation density is high: it contains 31 percent of India's population in about 18 percent of the total geographical area.